Analisis perbandingan revenueand profit sharing pada sistemmudharabah pada PT. BPRS Hijrah Rahmah Samarinda (Mazahib, 2014)
This research aims at comparingthe methods of profit sharing with revenue sharing insyari’ah financial principles. Syari'ah financial principles in this issue are mudharabah. The study was conducted at PT. BPRS Hijrah Rahmah, Samarinda. Besides comparing between profit sharing and revenew sharing, italso teststhe suitability of the fatwa of the Council of Indonesian Ulama (Majlis UlamaIndonesiaor MUI) No. 15/DSN-MUI/IX/2000 about principles of operationsin Islamic Financial Institutions. This study found that PT. BPRS Hijrah Rahmah uses revenue sharing more frequently than profit sharing. This is due to make it easier to calculate through revenue sharing rather than profit sharing.